2007
DOI: 10.1111/j.1365-2915.2007.00673.x
|View full text |Cite
|
Sign up to set email alerts
|

Haemocyte population and ultrastructural changes during the immune response of the mosquito Culex quinquefasciatus to microfilariae of Wuchereria bancrofti

Abstract: Haemocytes circulating in the haemolymph protect insects against pathogens that enter the haemocoel. Changes in haemocyte morphology and differences in haemocyte counts during the immune response of Culex quinquefasciatus Say (Diptera: Culicidae) to microfilariae of Wuchereria bancrofti (Cobbold) (Spirurida: Onchocercidae) were investigated in the present study. The mean number of total haemocytes was significantly elevated in infected mosquitoes (P<0.001), reaching a peak on the third day post-infection. Diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 21 publications
(39 reference statements)
2
7
1
Order By: Relevance
“…2B). Similar observations were reported by Brayner et al (2007) who found that GRs, PLs and OEs presented morphological alterations indicative of innate immunological activation in mosquitoes infected with W. bancrofti, while PRs did not show any ultrastructural alteration. Similarly, Faraldo et al (2008) reported that at 24-h post-injection of Saccharomyces cerevisae yeast cells to Chrysomya megacephala cell debris and some free yeast cells were surrounded by granules and electron dense PLs which were probably initiating the nodulation process.…”
Section: Ultrastructural Changes In a Ipsilon Haemocytessupporting
confidence: 89%
See 1 more Smart Citation
“…2B). Similar observations were reported by Brayner et al (2007) who found that GRs, PLs and OEs presented morphological alterations indicative of innate immunological activation in mosquitoes infected with W. bancrofti, while PRs did not show any ultrastructural alteration. Similarly, Faraldo et al (2008) reported that at 24-h post-injection of Saccharomyces cerevisae yeast cells to Chrysomya megacephala cell debris and some free yeast cells were surrounded by granules and electron dense PLs which were probably initiating the nodulation process.…”
Section: Ultrastructural Changes In a Ipsilon Haemocytessupporting
confidence: 89%
“…While, the data shown in Table 2 are in disagreement with those detected by Abu El-Magd and ElKifl (1993) who found that nematode decreased the PLs and GRs of S. littoralis larvae after 12 h of infection. Also, the results were reported by Brayner et al (2007) are in contrast with the present results. They investigated that when Culex quinquefasciatus Say infected with microfilariae of Wuchereria bancrofti, the mean number of total haemocytes was significantly elevated reaching a peak on the third day post-infection.…”
Section: B Thuringiensiscontrasting
confidence: 85%
“…Studies that have recognized additional hemocytes types in mosquitoes also report that oenocytoids and prohemocytes comprise only a small proportion of the total hemocytes in circulation [23-25,36]. Collectively, these data agree with data from D. melanogaster, several species of Lepidoptera and other arthropods, where consistently only a small proportion of circulating hemocytes are identified as oenocytoids (called crystal cells in Drosophila ) and prohemocytes [15,43,48].…”
Section: Circulating Hemocyte Numberssupporting
confidence: 72%
“…The number of circulating hemocytes in adult mosquitoes decreases with age [27,28,35,36], increases after blood feeding [37,38], and depending on the mosquito-pathogen combination, may increase, decrease or remain the same following infection [10,16,28,35,36,39,40]. While these trends are clear, the total number of hemocytes in circulation has recently received a significant amount of attention (Fig.…”
Section: Circulating Hemocyte Numbersmentioning
confidence: 99%
“…Deformation is essential for red blood cells to perform their physiological functions in the circulation of capillary blood vessels and thus affects the rheology of the blood [68]. The deformations of white blood cells and red blood cells can, respectively, affect the immune response and the oxygen load release [9, 10]. The synthetic microcapsules with polymerized interfaces are designed for drug delivery, cosmetic production, and other technical usages [11, 12].…”
Section: Introductionmentioning
confidence: 99%